Augmented reality mobile app development for all. (January 2018) - Mota, José Miguel; Ruiz-Rube, Iván; Dodero, Juan Manuel; Arnedillo-Sánchez, Inmaculada
Highlights: Classification of authoring tools to develop e-learning activities with AR. Framework to support technologies such as Augmented Reality and Learning analytics. Visual programming language to overcome the barriers to develop mobile applications. Results of an evaluation with educators and students. Graphical abstract: Abstract: Lack of programming skills is a barrier to the engagement of teachers in the development and customisation of their own applications. Visual Environment for Designing Interactive Learning Scenarios (VEDILS), a visual tool for designing, customising and deploying learning technologies, provides teachers with a development environment with a low entry threshold. Current mobile devices are equipped with sensors and have sufficient processing power to use augmented reality technologies. Despite the heavy use of mobile devices in students' lives, the use of augmented reality mobile applications as learning tools is not widespread among teachers. The current work presents a framework comprising the development tool and a method for designing and deploying learning activities. It focuses on the augmented reality components of the authoring tools, which allow users to create their own mobile augmented reality learning apps. It also present the results of the evaluation of the framework with 47 third-level educators, and two case studies of classroom implementations of mobile augmented reality apps developed by these educators. The results illustrate the suitability of the framework and authoring tool for supporting users without programming skills in developing their own apps.